Islam, society, and politics in Central Asia - Jones, Pauline (Professor of political science); Project Muse. (Pittsburgh, Pa. : University of Pittsburgh Press, 2017)
During the 1990s, there was a consensus that Central Asia was witnessing an Islamic revival after independence, and that this would follow similar events throughout the Islamic world in the prior two decades, which had negative effects on both social and political development. Twenty years later, we are still struggling to fully understand the transformation of Islam in a region that's evolved through a complex and dynamic process, involving diversity in belief and practice, religious authority, and political intervention. This volume sheds light on these crucial questions by bringing together an international group of scholars who offer a fresh perspective on Central Asian states and societies. --
Introduction: Reassessing the "Islamic Revival" in Central Asia / Pauline Jones -- The social significance of Islam in post-Soviet Central Asia: the case of Kyrgyzstan / Rouslan Jalil -- Beyond piety: self-related Muslims in Uzbekistan / Svetlana Peshkova -- Radical Islam from below: The Mujaddidiya and Hizb-ut-Tahrir in the Ferghana Valley / Vera Exnerova -- Engineering Islam: Uzbek state policies of control / David Abramson and Noah Tucker -- Subversives and saints: Sufism and the state in Central Asia / Emily O'Dell -- Unregistered: gray spaces in the Soviet regulation of Islam / Eren Murat Tasar -- The ascendance of orthodoxy: nation building and religious pluralism in Central Asia / Noor O'Neill Borbieva -- Islam, religious elites, and the state in post-Civil War Tajikistan / Tim Epkenhans -- When religion resorts to violence explaining variation in religious-based mobilization in Kyrgyzstan / Alisher Khamidov -- The localization of the Transnational Tablighi Jama'at Network in Kyrgyzstan / Mukaram Toktogulova -- Transnational Islamic banks and local markets in Central Asia / Aisalkyn Botoeva -- Studying Islam abroad: pious enterprises and educational aspirations of young Tajik Muslims / Manja Stephan-Emmrich -- Central Asia as part of the Islamic core / Pauline Jones.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Islam and politics -- Asia, Central; Muslims -- Asia, Central; Islam -- Asia, Central; Musulmans -- Asie centrale; Islam -- Asie centrale; RELIGION / Islam / General; Islam; Islam and politics; Muslims; Central Asia; Religionspolitik; Religionsausübung; Vergleichende Forschung; Islam; Sufismus; Religiöser Wandel; Zentralasien; Electronic books